2006
DOI: 10.1007/s11481-006-9019-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opioid Tolerance and Withdrawal on the Immune System

Abstract: Review of the robust literature using acute drug injection paradigms points clearly to the conclusion that morphine is immunosuppressive. In contrast, studies of the effect of subacute or chronic administration of morphine on immune function is limited, with variable results. In some cases tolerance to the immunosuppressive effects of the drug is clearly demonstrated, but in other cases, selected immune parameters do not demonstrate tolerance. Discrepancies in findings may result from differences in species or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…Opioid use and abuse renders individuals susceptible to infection (see Eisenstein et al, 2006;Wang et al, 2008) and a variety of mechanisms have been proposed to explain how opioids suppress the immune system. These mechanisms include effects on both the innate and adaptive branches of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid use and abuse renders individuals susceptible to infection (see Eisenstein et al, 2006;Wang et al, 2008) and a variety of mechanisms have been proposed to explain how opioids suppress the immune system. These mechanisms include effects on both the innate and adaptive branches of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…There is a general agreement that morphine administration leads to suppression of several immune parameters (31). Thomas et al have shown that opioids directly induce suppression of CTL activity when cultured with splenocytes (32).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, administration of morphine has been suggested to suppress specific immune responses and the alteration of the course of microbial infection [1,2]. Withdrawal from morphine has been suggested to cause a stronger suppression of immune response compared to morphine addiction [3,4,5]. Most drug abusers experience periods of arbitrary withdrawal.…”
Section: Introductionmentioning
confidence: 99%